Survei Penatalaksanaan Pasca Cedera Olahraga Dengan Pengobatan Tradisional Atau Dengan Pengobatan Modern Pada Atlet Olahraga Permainan Bola Besar Kota Malang - Nofan Saputra; Rias Gesang Kinanti; Ahmad Abdullah (Gerak: Journal of Physical Education, Sports, and Health, 2022)
People in choosing treatment of injuries in sports is still use traditional methods. The traditional method is sangkal putung massage. Sangkal putung is believed as the cheaper and faster treatment than sports rehabilitation which takes a relatively long time. This study aims to determine how the post-injury rehabilitation with modern or traditional methods for athletes in Malang City. This study uses a quantitative descriptive research design with a survey approach. The population in this study were athletes of the big ball game in Malang City and the sample was 21 athletes taken by the Nonprobability Sampling technique, with a stratified random sampling type with a portion of 25%. This study used a questionnaire instrument with a Likert scale. The collected data analyzed by categorizing using the mean and standard deviation. The results of data analysis showed that the level of knowledge of athletes in big ball games regarding to sports injuries at KONI Malang City was that most of the athletes were in the poor category or using traditional massage sangkal putung, while the rest were in moderate and good category. The conclusion of this study is that most athletes still use traditional massage sangkal putung for treatment in post-injury sports.